Monitoring freshly poured concrete using ultrasonic waves guided through reinforcing bars - Sharma, S.; Mukherjee, Abhijit (Elsevier Ltd, 2015)
Durability and strength of mature concrete can be judged a great deal from its properties when it is freshly poured. This paper demonstrates an ultrasonic in-situ monitoring technique for freshly poured concrete. The solidification and curing of freshly poured concrete is monitored through the propagation of ultrasonic waves in waveguides such as steel reinforcing bars. As concrete solidifies and cures, more wave energy escapes into the surrounding concrete resulting in signal attenuation. RC beam specimens are monitored with carefully selected ultrasonic signal patterns during the first 24 h of setting of concrete. Destructive tests such as bar pull out and compressive strength are also performed at different stages of setting of concrete. The ultrasonic signals have been calibrated for determination of early age concrete properties.